Plasma Choline Concentration Is Positively Correlated with Visual Acuity in 18-Month Old Toddlers: Preliminary Findings. (29th May 2020) - Montgomery, Sarah; Rossen, Larissa; Zibrik, Deborah; Dyer, Roger; Oberlander, Tim; Lamers, Yvonne
Abstract: Objectives: Adequate dietary intake of key nutrients is critical for brain and eye development in the first 1000 days of life. In particular, docosahexaenoic acid (DHA) and lutein are known for their roles in the development of visual acuity during infancy and early childhood. Preliminary data suggest that choline may also play a role in visual acuity; however, little is known about choline's role in visual acuity during toddlerhood. We hypothesize thatbiomarkers for DHA, choline, and lutein status are positively correlated with visual acuity in toddler-aged children. Methods: We studied cross-sectional baseline data from participants aged 18 months ± 2 weeks enrolled in a partially randomized controlled trial investigating associations between feeding patterns, nutrient biomarker status, and neurodevelopmental outcomes. Participants were recruited in Metro Vancouver, Canada. Visual acuity was measured using the Cardiff Acuity test with the logarithm of the minimum angle of resolution (LogMAR) as the measure of visual acuity. The child's confidence in test completion was rated using a 5-point Likert scale; test results with confidence scores below 3 were excluded from further analyses. Results: Sixty-nine toddlers, with preliminary data available at the time of analysis, had an equal distribution of males and females, 68% were the first-born child, and 55%, 19%, and 26% were of European, Chinese or other ethnicity, respectively. Preliminary (unadjusted) findings showed a positive correlation between plasma choline and visual acuity (rho = 0.33, P < 0.05). No significant correlations were observed between visual acuity and DHA concentration (as a percentage of total fatty acids from red blood cells) nor between visual acuity and plasma lutein concentration. Conclusions: Plasma choline may be positively associated with visual acuity at 18 months of age. These preliminary findings require confirmation in a larger sample size and testing of the causality of this relationship in a dose-dependency trial. Acknowledgment: We are grateful for Dr. Margaret Woodhouse's guidance in the methodology of the Cardiff Acuity test. Funding Sources: This study is supported by The University of British Columbia, and the British Columbia Children's Hospital Research Institute and is funded by Société des Produits Nestlé S.A.